Surface N-glycoproteome patterns reveal key proteins of neuronal differentiation - Tyleckova, Jirina; Valekova, Ivona; Zizkova, Martina; Rakocyova, Michaela; Marsala, Silvia; Marsala, Martin; Gadher, Suresh Jivan; Kovarova, Hana (Journal of proteomics, 2016)
UNLABELLED: Pluripotent stem cell-derived committed neural precursors are an important source of cells to treat neurodegenerative diseases including spinal cord injury. There remains an urgency to identify markers for monitoring of neural progenitor specificity, estimation of neural fate and follow-up correlation with therapeutic effect in preclinical studies using animal disease models. Cell surface capture technology was used to uncover the cell surface exposed N-glycoproteome of neural precursor cells upon neuronal differentiation as well as post-mitotic mature hNT neurons. The data presented depict an extensive study of surfaceome during neuronal differentiation, confirming glycosylation at a particular predicted site of many of the identified proteins. Quantitative changes detected in cell surface protein levels reveal a set of proteins that highlight the complexity of the neuronal differentiation process. Several of these proteins including the cell adhesion molecules ICAM1, CHL1, and astrotactin1 as well as LAMP1 were validated by SRM. Combination of immunofluorescence staining of ICAM1 and flow cytometry indicated a possible direction for future scrutiny of such proteins as targets for enrichment of the neuronal subpopulation from mixed cultures after differentiation of neural precursor cells. These surface proteins hold an important key for development of safe strategies in cell-replacement therapies of neuronal disorders. BIOLOGICAL SIGNIFICANCE: Neural stem and/or precursor cells have a great potential for cell-replacement therapies of neuronal diseases. Availability of well characterised and expandable neural cell lineage specific populations is critical for addressing such a challenge. In our study we identified and relatively quantified several hundred surface N-glycoproteins in the course of neuronal differentiation. We further confirmed the abundant changes for several cell adhesion proteins by SRM and outlined a strategy for utilisation of such N-glycoproteins in antibody based cell sorting. The comprehensive dataset presented here demonstrates the molecular background of neuronal differentiation highly useful for development of new plasma membrane markers to identify and select neuronal subpopulation from mixed neural cell cultures.
Keywords: Membrane Glycoproteins; proteiny nervové tkáně; Cell Line; nervové kmenové buňky; Cell Differentiation; lidé; buněčná diferenciace; membránové glykoproteiny; buněčné linie; Cells, Cultured; Nerve Tissue Proteins; Neural Stem Cells; kultivované buňky; Humans